GARP is a key molecule for mesenchymal stromal cell responses to TGF-β and fundamental to control mitochondrial ROS levels. (19th February 2020) - Carrillo-Gálvez, Ana Belén; Gálvez-Peisl, Sheyla; González-Correa, Juan Elías; Haro-Carrillo, Marina; Ayllón, Verónica; Carmona-Sáez, Pedro; Ramos-Mejía, Verónica; Galindo-Moreno, Pablo; Cara, Francisca E.; Granados-Principal, Sergio; Muñoz, Pilar; Martin, Francisco; et al.
Abstract: Multipotent mesenchymal stromal cells (MSCs) have emerged as a promising cell therapy in regenerative medicine and for autoimmune/inflammatory diseases. However, a main hurdle for MSCs-based therapies is the loss of their proliferative potential in vitro. Here we report that glycoprotein A repetitions predominant (GARP) is required for the proliferation and survival of adipose-derived MSCs (ASCs) via its regulation of transforming growth factor-β (TGF-β) activation. Silencing of GARP in human ASCs increased their activation of TGF-β which augmented the levels of mitochondrial reactive oxygen species (mtROS), resulting in DNA damage, a block in proliferation and apoptosis. Inhibition of TGF-β signaling reduced the levels of mtROS and DNA damage and restored the ability of GARP −/low ASCs to proliferate. In contrast, overexpression of GARP in ASCs increased their proliferative capacity and rendered them more resistant to etoposide-induced DNA damage and apoptosis, in a TGF-β-dependent manner. In summary, our data show that the presence or absence of GARP on ASCs gives rise to distinct TGF-β responses with diametrically opposing effects on ASC proliferation and survival. : Abstract : Silencing of glycoprotein A repetitions predominant (GARP) in adipose-derived mesenchymal stromal cells (ASCs) increases the activation of transforming growth factor-β (TGF-β), resulting in mitochondrial reactive oxygen species-dependent DNA damage, inhibition of proliferation, and apoptosis. In contrast, overexpression of GARP induces a TGF-β response characterized by an increased resistance to DNA damage, increased proliferation, and a reduction in apoptosis. We show that GARP is critical in controlling TGF-β activation/signaling in ASCs during in vitro expansion.